Explosive compaction of Al2O3 nanopowders. Issue 7 (15th May 2016) - Wang, Bingfeng; Xie, Fangyu; Li, Zhicheng; Zhang, Hong
Abstract: Dense bulk alumina (Al2 O3 ) has been prepared by explosive compaction and its microstructure has been investigated by optical microscopy, Raman spectroscopy, scanning electron microscopy and transmission electron microscopy. The average microhardness of the alumina compact is about 171 HV0.025. Ultra-thin alumina films with glassy (translucent) appearance formed during the explosive compaction process. Nanograin Al2 O3 particles are covered by amorphous Al2 O3 which help to achieve a dense microstructure by promoting interparticles bonding. Phase transformation from γ-Al2 O3 to α-Al2 O3 during the explosive compaction process has been confirmed. Formation of the alumina compact is due to the large cooling rate and the high pressure during the explosive compaction.